“Every method seems to have its problems”- perspectives on side effects of hormonal contraceptives in Morogoro Region, Tanzania - Chebet, Joy J.; McMahon-Rössle, Shannon A.; Greenspan, Jesse A.; Mosha, Idda H.; Callaghan-Koru, Jennifer A.; Killewo, Japhet; Baqui, Abdullah H.; Winch, Peter J. (BMC women's health, 2015)
Family planning has been shown to be an effective intervention for promoting maternal, newborn and child health. Despite family planning's multiple benefits, women's experiences of - or concerns related to - side effects present a formidable barrier to the sustained use of contraceptives, particularly in the postpartum period. This paper presents perspectives of postpartum, rural, Tanzanian women, their partners, public opinion leaders and community and health facility providers related to side effects associated with contraceptive use.
Gesehen am 13.11.2020